Rainfall Intensity Temporal Patterns Affect Shallow Landslide Triggering and Hazard Evolution. Issue 1 (17th January 2020) - Fan, Linfeng; Lehmann, Peter; Zheng, Chunmiao; Or, Dani
Abstract: A characteristic of rainfall‐induced landslides is the gradual loading by infiltrating rainwater that weakens the soil mantle and could progress to abrupt soil mass release. The temporal patterns of similar rainfall amounts affect the hydrological response of a catchment and thus influence landslide dynamics. We use a novel catchment scale landslide hydromechanical triggering model to systematically study how different asymmetric distributions of rainfall intensities affect landslide dynamics and hazard evolution. Evaluating rainfall events with similar durations and total amounts shows that early rainfall peak intensity exerts stronger destabilizing effects, relative to delayed rainfall peak intensity. Intense rainfall events reduce landslide triggering relative to uniform‐intensity rainfall events due to reduced water infiltration. With advances in highly resolved and real‐time precipitation observations, the study offers a means for improving prediction of landslide timing and hazard evolution and identifying hydrological scenarios that enhance landslide activity. Plain Language Summary: Rainfall‐induced landslide triggering is associated with rainwater infiltration that may load and weaken soil mantle and lead to abrupt soil mass release. Temporal rainfall patterns may affect the infiltration process and control landslide dynamics and hazard evolution. We investigate the effects of rainfall temporal patterns of similar durations and total amounts on landslide dynamics by forcing a catchment scale landslide hydromechanical triggering (LHT) model with artificial rainfall time series with different timing and magnitudes of peak intensity. With identical duration and total amount, rainfall patterns with early peak intensity promote landslide activity compared with late peak intensity. High peak rainfall intensities reduce total rainwater infiltration and thus hinder landslide triggering relative to more uniform rainfall time series. With the rapid advances in high spatiotemporal resolution precipitation measurements, the results of this study may improve landslide prediction and provide useful guidelines for real‐time landslide early warning. Key Points: Rainfall intensity temporal patterns influence simulated infiltration amounts and thus affect timing and volumes of shallow landslides With identical rainfall amount and duration, early peak rainfall intensity contributes to greater instability than later peak intensity Uniform‐intensity rainfall events promote landslide activity relative to extreme rainfall of similar total rainfall amount and duration